设函数f(x)和g(x)都可导,且[img=120x23]17da62a1934dada.jpg[/img]则函数[img=130x30]17da62a1a32427c.jpg[/img]的导数存在
举一反三
- 设函数f(x)和g(x)都可导,且[img=120x23]17e0a7a197a70a7.jpg[/img]则函数[img=130x30]17e0a7a1a0c51d4.jpg[/img]的导数存在
- 设函数f(x)和g(x)都可导,且[img=120x23]17e43679ff3947f.jpg[/img]则函数[img=130x30]17e4367a071b6b0.jpg[/img]的导数存在
- 设[img=28x19]17da41b38e91a03.jpg[/img]为可导函数,则[img=63x37]17da426f632f014.jpg[/img]的导数是( ) A: f(x) B: f(x)+C C: f '(x) D: f '(x)+C
- 函数f(x)在[img=17x17]1803d281f3e9e10.png[/img]处左右导数都存在,则f(x)在[img=17x17]1803d281f3e9e10.png[/img]可导。
- 设X的密度函数为f(x),分布函数为F(x),且f(x)是偶函数,则有 A: [img=235x53]1803b3ba8e4e24a.png[/img] B: [img=248x66]1803b3ba9822ce1.png[/img] C: F(−x)= F(x) D: F(−x)=2F(x)−1